ARUGA improving the well-being of children undergoing cancer treatments through the synergetic approach of a biophilic healing environment - Cruz, Daniella Ivan A.; Rinen, Richard Martin E. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
Cancer remains one of the leading causes of death for children and adolescents worldwide. This even worsened during the pandemic as it brought cancer patients into more difficult situations. Visiting the hospital for various treatments could increase the patient’s risk of the COVID-19 infection whereas staying at home could increase the disease’s progression. Children with cancer are also deemed most vulnerable to the virus because of their age, comorbidities, and overall state due to their disease.
Although the Philippine Society of Medical Oncology (PSCMO) released guidelines on how oncologists can commence the treatment of cancer patients during the pandemic, it failed to entail how the surrounding environment of the patients can affect their healing process. The setting in which cancer patients reside is crucial because they frequently undergo medical procedures that can cause both short- and long-term discomfort and can feel a variety of unfavorable emotions, including stress, anxiety, and uncertainty.
This design project aims to identify how cancer care facilities can be improved and seek architectural interventions that can help maximize the healing potential of children undergoing cancer treatments. Although there are studies on how the optimal healing environment can be introduced to cancer patients, there remains a gap in the literature of designs for cancer care facilities that are specifically for children with cancer and their families. By applying techniques, concepts, and architectural elements supported by Optimal Healing Environment (OHE) and Biophilic Design, this project intends to create a positive impact on the health and well-being of children with cancer, reduce their emotional stress, and support them in a positive manner. Since it also aims to adapt the modified spatial provisions and limitations of healthcare environments brought by the pandemic, this study can have a valuable contribution to the design of other healthcare facilities as well as provide additional guidelines to the PSCMO and other related health agencies.
include appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Cancer in children; Cancer -- Patients -- Hospital care; Health facilities